Elderly gastrointestinal conditions increase sterol bioaccessibility in a plant sterol-enriched beverage: adaptation of the INFOGEST method. Issue 8 (28th March 2022) - Miedes, Diego; Makran, Mussa; Barberá, Reyes; Cilla, Antonio; Alegría, Amparo; Garcia-Llatas, Guadalupe
Abstract : Elderly people suffer from a higher cardiovascular risk. Abstract : Elderly people suffer from a higher cardiovascular risk. Thus, the fortification of foods with plant sterols (PSs), which have a cholesterol-lowering function, could be of great interest for this target group. To date, no studies have analyzed how the gastrointestinal conditions of the elderly affect PS bioaccessibility. Therefore, this study evaluated the impact of the adaptation of the gastric phase alone and in combination with the intestinal phase on sterol bioaccessibility. For this purpose, the standardized INFOGEST 2.0 method previously adapted for sterol bioaccessibility evaluation in healthy adults was applied to PS-enriched milk-based fruit beverages, examining changes in enzyme activity, incubation time, agitation and pH, based on elderly physiology. The results suggest that the specific gastrointestinal conditions of the elderly could increase absorption of PSs, since their bioaccessibility (%) in a PS-enriched milk-based fruit beverage was significantly increased compared with that in adults (14.95 ± 0.33 vs . 7.96 ± 0.26), also indicating that these conditions increase the bioaccessibility of the beverage's own cholesterol (61.25 ± 2.91 vs. 20.86 ± 2.79). These data support the recommendation of foods of this type for the elderly who can benefit from the increase in bioaccessibility of PSs to have an improved potential cholesterol lowering effect, thus decreasing their risk of cardiovascular disease. However, the performance of subsequent in vivo tests to confirm these results is necessary.